Pengaruh Inflasi Dan Suku Bunga Terhadap Retrun Saham Dengan Profitabilitas Sebagai Variabel Moderating Pada Perusahaan Industri Barang Konsumsi (Subsektor Rokok) Tahun 2019-2021 - Febriyanto; Karnila Ali; Mutiara Wika Azyaza (Universitas Muhammadiyah Metro, 2024)
This study aimed at determining whether there was an effect of inflation and interest rates retrun stocks with profitability as a moderating variable. This research method applied documentation techniques with a quantitative approach. It was conducted at the cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX) which were still actively listed during the 2019-2021 period. The research sample was taken purposively which totally from 4 companies. The data of this study were analyzed by the classical assumption test, namely the normality test, multicollinearity test, heteroscedasticity test, and auto correlation test. To test the hypothesis, this study utilized panel data regression test with the common effect model technique, fixed effect model, and random effect model. Selection of the technique was done by doing the chow test, hausman test, lagrange multiplier test and test the moderating variable. Based on the results of the study showed that 1) The inflation has no significant effect on stock returns. 2) The interest rates have no significant effect on stock returns. 3) The profitability has a significant effect and strengthens the relationship between inflation and stock returns. 4) The profitability has a significant effect and strengthens the relationship between interest rates and stock returns.